Semantic interoperability in the internet of things - state-of-the-art and prospects. (18th March 2021) - Ahamed, Jameel; Chishti, Mohammad Ahsan
Internet of things (IoT) is generally referred to as an internet world of little things with limited storage and processing ability, but facing communication, security, privacy, and interoperability issues. Further, device, network, platform, syntactic, and semantic are the major interoperability issues in the internet of things. Smart objects, termed as interconnected devices, generate a huge chunk of heterogeneous data and its processing, as well as usage, becomes the challenge in IoT. Therefore, this heterogeneous data is semantically annotated using linked vocabularies to make it interoperable information. The main aim of this article is to have a deep understanding of semantic interoperability that will help in sharing heterogeneous data through the development of knowledge-based systems or common ontologies.